A Biodiesel Production Technology from Used Cooking Oil: A Review - Erwan Adi Saputro; Ahmad Rizaldi; Tahan Simamora; Nove Kartika Erliyanti; Rachmad Yogaswara (IPTEK The Journal for Technology and Science, 2022)
Used cooking oil is widely considered waste because it can damage the environment and cause health problems. Meanwhile, used cooking oil can be used as a substitute raw material for Crude Palm Oil (CPO) in Indonesia's national biodiesel program. Indonesia has a remarkable ability to use used cooking oil as a raw material for making biodiesel. If the 1.2 million kiloliters of biodiesel made from CPO raw materials are exchanged with used cooking oil raw materials, it can save approximately Rp. 4.2 trillion. There are various process technologies in making biodiesel, including microemulsion, pyrolysis, and transesterification. Transesterification is a process in which triglycerides and methanol are reacted to create biodiesel and glycerol as a by-product. Transesterification using a homogeneous catalyst has advantages such as lower cost, relatively short processing time, and higher yield of biodiesel products. Transesterification using a homogeneous catalyst has the disadvantage of a more complex separation. This literature study aims to explain the method for biodiesel production and becomes a reference in terms of process selection in biodiesel manufacturing plants, especially from used cooking oil as raw material.